Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/bies.20514
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of intermediate filaments: from tissues to single filaments and back

Abstract: The animal cell cytoskeleton consists of three interconnected filament systems: actin-containing microfilaments (MFs), microtubules (MTs), and the lesser known intermediate filaments (IFs). All IF proteins share a common tripartite domain structure and the ability to assemble into 8-12 nm wide filaments. Electron microscopy data suggest that IFs are built according to a completely different plan from that of MFs and MTs. IFs are known to impart mechanical stability to cells and tissues but, until recently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 92 publications
(136 reference statements)
9
79
0
7
Order By: Relevance
“…Recent measurements show that the structure of IFs leads to single filament mechanics that are different from both actin and microtubules (Guzman et al, 2006;Kiss et al, 2006;Kreplak and Fudge, 2007;Kreplak et al, 2005). Imaging measurements suggest that the persistence length for vimentin filaments is on the order of 1 μm, one order of magnitude smaller than for F-actin and three orders of magnitude smaller than for microtubules (Mucke et al, 2004).…”
Section: B Mechanics Of Ifsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent measurements show that the structure of IFs leads to single filament mechanics that are different from both actin and microtubules (Guzman et al, 2006;Kiss et al, 2006;Kreplak and Fudge, 2007;Kreplak et al, 2005). Imaging measurements suggest that the persistence length for vimentin filaments is on the order of 1 μm, one order of magnitude smaller than for F-actin and three orders of magnitude smaller than for microtubules (Mucke et al, 2004).…”
Section: B Mechanics Of Ifsmentioning
confidence: 99%
“…The particular architecture of IFs is important for understanding their unique mechanical properties Kreplak and Fudge, 2007). The assembly of IFs is quite complex and distinct from the assembly process of F-actin or microtubules (Herrmann and Aebi, 1998;Herrmann et al, 1999).…”
Section: A Introductionmentioning
confidence: 99%
“…Furthermore, -keratin materials have different forms in nature, varying from the filamentous type of hair and wool to the laminations of cattle horn. The specific form of -keratin is thought to be mainly determined by the network of hydrogen-bonds (Kitchener and Vincent, 1987), covalent disulphide bonds (Hearle, 2000) and intermolecular cross-links such as ionic interactions and van der Waals bonds (Fraser et al, 1986;Parry, 1996;Kreplak and Fudge, 2007). Previous experimental studies found a progressive increase of water mobility and a decrease in structural rigidity of -keratin with hydration (Speakman, 1928;King, 1945).…”
Section: Hydration Dependence Of Mechanical Propertiesmentioning
confidence: 99%
“…In contrast, intermediate filaments exhibit strain hardening at high tensile strains without rupture. 7,9,12 Every cell type is composed of different types and amounts of specific cytoskeleton fibers. Simple epithelia, such as the pancreatic cancer cells we investigated here, have a well-developed keratin intermediate filament network in addition to actin and microtubules.…”
Section: Introductionmentioning
confidence: 99%